1996
DOI: 10.1083/jcb.133.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Dictyostelium mutants lacking multiple classic myosin I isoforms reveal combinations of shared and distinct functions.

Abstract: Abstract. Dictyostelium cells that lack the myoB isoform were previously shown to exhibit reduced efficiencies of phagocytosis and chemotactic aggregation ("streaming") and to crawl at about half the speed of wild-type cells. Of the four other Dictyostelium myosin I isoforms identified to date, myoC and myoD are the most similar to myoB in terms of tail domain sequence. Furthermore, we show here that myoC, like myoB and myoD, is concentrated in actin-rich cortical regions like the leading edge of migrating ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
187
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(194 citation statements)
references
References 59 publications
(176 reference statements)
6
187
1
Order By: Relevance
“…Experiments performed in multiple eukaryotic model systems have implicated class I myosins in various aspects of membranerelated events including phagocytosis (29)(30)(31)(32)(33), endocytosis (34)(35)(36)(37), exocytosis (38,39), and membrane recycling (40). Although our current data set does not allow us to rule out the possibility that perturbations in membrane trafficking may contribute to the changes in membrane tension observed in our experiments, our results do provide strong support for a model where class I myosins play a direct role in the control of membrane tension, by contributing to adhesion between the plasma membrane and underlying actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments performed in multiple eukaryotic model systems have implicated class I myosins in various aspects of membranerelated events including phagocytosis (29)(30)(31)(32)(33), endocytosis (34)(35)(36)(37), exocytosis (38,39), and membrane recycling (40). Although our current data set does not allow us to rule out the possibility that perturbations in membrane trafficking may contribute to the changes in membrane tension observed in our experiments, our results do provide strong support for a model where class I myosins play a direct role in the control of membrane tension, by contributing to adhesion between the plasma membrane and underlying actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…To address V-1's role in this actin-based process, we compared the rate of uptake of the nondigestible fluid phase marker TRITC-dextran in WT and V-1-null cells. Of note, the rate of accumulation of this marker within cells during the first ∼60 min after its addition to the medium accurately reports the rate of fluid phase endocytosis because the time interval between the uptake and exoctyosis of nondigestible markers in Dictyostelium, which lack a rapid recycling component, is ∼60 min (41). Fig.…”
Section: Vegetative V-1-null Cells Exhibit a Defect In Macropinocytosmentioning
confidence: 99%
“…At this stage, Dictyostelium amoebae exhibit their highest rate of motility, which is approximately two to four times faster than the rate exhibited by vegetative cells (41,43,44). Ripple-stage cells were then harvested by trituration and allowed to attach at low density on chamber slides for 20 min.…”
Section: Vegetative V-1-null Cells Exhibit a Defect In Macropinocytosmentioning
confidence: 99%
“…Nevertheless, it has been shown that phagocytosis (7) and references therein) as well as part of axonal transport (8) and exocytosis (9) are actin-based movement. Endocytosis in yeast (10), vertebrates (11) and amoebae (12,13), polarized secretion in yeast (14), and fungi (15), vacuole inheritance in yeast (16), contractile vacuole function in amoebae (17), as well as blastoderm cellularization and cytoplasmic transport of particles in Drosophila (18,19), require specific myosin motors. Myosin V has now been shown to power the redistribution of melanosomes in mouse melanocytes (20,21), as well as in fish and Xenopus melanophores (22,23).…”
Section: Soldati Geissler and Schwarzmentioning
confidence: 99%
“…Disruptions of single myosin I genes showed only subtle alterations of cell motility, and multiple disruptions had to be performed to induce stronger phenotypic impairments. Different combinations of double and even triple mutations of myoB, myoC, myoD, or myoA resulted in strains impaired to different extents in macropinocytosis and motility, highlighting the potentially high degree of functional redundancy (12,13,75). It is important to note that in a similar way, disruption of the genes for multiple actin-binding proteins was necessary to reveal strong phe-Exploring the Myosin Repertoire 399 notypic alterations (76), indicating that a certain level of redundancy is probably inherent to components of the actin cytoskeleton and associated vital functions.…”
Section: Phylogenetic Analysis Shows the Newcomer Myok (See "A Potentmentioning
confidence: 99%